Social Support Moderates the Negative Association Between Reduced Driving and Life Satisfaction in Older Adults. (November 2020) - Jones, Vanya C.; Johnson, Renee M.; Borkoski, Carey; Rebok, George W.; Gielen, Andrea C.; Soderstrom, Carl; Molnar, Lisa J.; Pitts, Samantha I.; DiGuiseppi, Carolyn; Hill, Linda; Strogatz, David; Mielenz, Thelma J.; et al.
When older adults reduce their driving, there can be subsequent decreases in life satisfaction. In this cross-sectional study, we used baseline data from the multi-site Longitudinal Research on Aging Drivers (LongROAD) study to examine whether social support moderates the negative association between reduced driving and life satisfaction. The outcome variable was life satisfaction, and the main predictor variable was past-year reduced driving (yes/no). Emotional, instrumental, and informational social support were measured using PROMIS v2.0 (Patient-Reported Outcomes Measurement Information System) items. We used generalized linear regression models to examine how social support moderated the association between reduced driving and life satisfaction. Statistical adjustment for social support attenuated the negative effect of reduced driving on life satisfaction by ~10% for all three types of social support.